Regional Soil Patterns as Indicators of Late Cenozoic Change in the Critical Zone: A Baseline Synthesis for the Landscapes of Peninsular India - Yanni Gunnell; Nicolas Durand; Shanti Pappu (Earth Science, Systems and Society)
Regolith across the South Indian shield has not previously been mapped. Here we provide a diagnosis of directional and lasting climate change from humid to semi-arid since the late Cenozoic based on evidence provided by mosaics of 1) residual, 2) colluvial and 3) alluvial soils across 700,000 km2 of southern peninsular India. Results are inferred from a systematic geomorphological and palaeoenvironmental interpretation of 1:250,000 scale legacy soil maps at order to subgroup level, complemented by field surveys and controls of soil parent material—i.e., regolith. The inventory highlights two generations of residual soils: 1) deep Lixisols, hosting low-activity clays and large iron hydroxide concentrations indicative of humid conditions in the geological past; and 2) shallow Luvisols containing high-activity clays and large stocks of exchangeable bases, indicative of drier conditions compatible with the modern climate. Where still present, the relict Lixisol inliers straddle drainage divides and are in the final stages of being thinned or fully stripped by headward stream erosion. They are being replaced by the Luvisols over shallow weathering fronts. Colluvial and alluvial soils, including widespread Vertisols, are used as tools for detecting and mapping different generations of Quaternary flood deposits: fluvial terraces, coastal fan-deltas, and shallow upland palaeolakes. In a region mostly devoid of carbonate rock outcrops, the widely distributed pool of soils hosting abundant accumulations of pedogenic CaCO3 also reveals the magnitude of silicate bedrock weathering as a process for generating secondary calcium carbonate in the rock cycle, thereby highlighting an under-appreciated contribution to inorganic carbon sequestration in the global carbon cycle. The results and maps produced provide exploration tools for future, more systematic and coordinated investigations of the nature and chronology of Quaternary deposits in peninsular India. This includes assessing their potential for hosting different generations of prehistoric archaeological remains.